2016
DOI: 10.1186/s40677-016-0040-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of topographic and geological features on building damage caused by 2015.4.25 Mw7.8 Gorkha earthquake in Nepal: a preliminary investigation report

Abstract: Background: The 2015.4.25 Gorkha earthquake affected about eight million people in Nepal. Most injuries and loss of life were due to building collapse and damage. This work aims to investigate the topographical and geological effects on the severe damage caused by this earthquake. Findings: In one-week field investigation in the earthquake-affected areas, several severely damaged areas with different topographic and geological features were surveyed, as well as the site of Kaligandaki River landslide dam failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…Intensity and duration of seismic-induced ground shaking is mainly determined by earthquake magnitude, depth of hypocenter, distance from the epicenter, medium of the seismic waves, topography and site-specific geology (Kramer, 1996;Wills and Clahan, 2006;Shafique and van der Meijde, 2015;Khan et al, 2017). The influence of the Earth's topography on seismic response has been observed and proven numerically and experimentally (Athanasopoulos et al, 1999;Sepúlveda et al, 2005;Lee et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Intensity and duration of seismic-induced ground shaking is mainly determined by earthquake magnitude, depth of hypocenter, distance from the epicenter, medium of the seismic waves, topography and site-specific geology (Kramer, 1996;Wills and Clahan, 2006;Shafique and van der Meijde, 2015;Khan et al, 2017). The influence of the Earth's topography on seismic response has been observed and proven numerically and experimentally (Athanasopoulos et al, 1999;Sepúlveda et al, 2005;Lee et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al (2008). Due to the unavailability of a wave speed model for the area, we assigned constant wave speeds (Vp=2800 m/s, Vs=1500 m/s) and density ρ=2300 kg/m 3 ) in the modelling, representative for upper crustal conditions (Taborda and Roten, 2015;Wang et al, 2016;Makra and Raptakis, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…There were several organizations involved in advocating the DRR, have several programs conducted through government and nongovernmental organizations, even though one study found that the perception and preparedness state for disaster prevention education is not properly placed (Tuladhar et al 2015). The long period dominant ground motion of Gorkha earthquake resulted relatively low damages in low rise buildings (Parajuli and Kiyono 2015), however, several other factors also contributed in structural damage (Sharma et al 2017;Wang et al 2016). Major themes of earthquake safety endorsed by all institutions and media were 'HIDE UNDER THE TABLE or BED' and 'DROP, COVER & HOLD'.…”
Section: Challenges and Gaps In Drr Implementationmentioning
confidence: 99%